The Role of Economics Teacher Forum in Improving Economics Teacher Performance in the City of Mojokerto - Hardinto, P; Rokhmani, L; Wafa, A A; Megasari, R (KnE Social Sciences, 2018)
The professionality of teachers can be known through the professional organization in which they participate. One of the professional organizations for teachers is Economics Teacher Forum or Musywarah Guru Mata Pelajaran (MGMP). In the forum, there are various programs where the stimulating and obstructing factors of performance should be accompanied by monitoring and evaluating system. The programmes need to be evaluated in order to know its benefits for the teachers’ performance. The monitoring and evaluation have become a process that is utilized in order to get an overview of the activity and performance of the forum itself in managing and holding activities consistently and continuously. The monitoring and evaluation are arranged to get references toward the factors implemented in the process per se. To know the role of the forum, this research is done by using Discrepancy Evaluation Model (DEM). The data collection uses observation, documentation, and interview techniques, with the subjects being the chairman, secretary, treasurer, field coordinator, and the members of Economics Teacher Forum of Mojokerto. The results showed the input components being effective and efficient through good organization management which is signified by the existence of clear articles of association and planned work programs. The process component were also effective and efficient with there being a routine agenda in every meeting. The consistent forum time frequency is shown by the consistency of forum members’ presence in each meeting. The output component is known by looking at the uniformity of the forum activities’ results with the planned work programs that indicates its effectiveness and efficient. It can be concluded that Economics Teacher Forum has a significant role in improving the performance of Mojokerto’s economics teachers. Keywords: Professional organization, Economics Teacher Forum, Role of the forum